(untitled) - Hotka, Dan (New York, 2007)
Enhance productivity and simplify database development tasks using Oracle SQL Developer and the detailed instructions in this Oracle Press guide. Written by experienced Oracle instructor Dan Hotka, Oracle SQL Developer Handbook shows you, step-by-step, how to put every feature of this new and exciting deployment tool to work for you. Inside, you'll learn to set up Oracle SQL Developer, establish database connections, and manage SQL, SQL*Plus, and PL/SQL scripts.
Keywords: Oracle (Computer file),SQL (Computer program language),Oracle (Chươg trình máy tính)